Investigations of Broach Wedges Wear - Legutko, Stanislaw; Wieczorowski, Kazimierz; Kedzierski, Tomasz (Manufacturing Technology Journal, 2009)
One of the most important problems in broaching technology is wedge wear one. The main trouble is to establish proper criterion of admissible wedge wear. Theoretical analysis of the loading of cutting wedge during broaching has been presented. Subsequent phases of broach wedges wear have been shown, on the base of authors' own investigations. The research has brought the authors to the conclusion that broach wear should be determined by other indicator thanks to which the state of the process can be easily and quickly defined. Such an indication is the condition of the surface layer being machined.
Keywords: broach; broaching; wedge wear